Protection of Children's Mental Development in Prostitution Environments: A Qualitative Study - Aghnis Syifa Solousyah; Cahniyo Wijaya Kuswanto (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
This study aims to examines the impact of prostitution environments on children's mental development and evaluates the effectiveness of child protection programs in Indonesia. Studies show that children living in prostitution environments are vulnerable to psychological trauma, anxiety, depression, and social stigmatization. This study aims to analyze these impacts, assess the effectiveness of child protection policies, and formulate an intervention model based on psychological, social, and educational support. Through qualitative methods, the study involved participants from the village secretary and the head of the Pamandangan RT, who were selected purposively. Data were collected through in-depth interviews, observations, and policy document analysis. The results showed that children in prostitution environments experience complex trauma due to violence, stigmatization, and family instability. Protective factors such as school support, mentoring, and the role of community leaders can increase children's resilience. However, the implementation of child protection policies is hampered by weak coordination between institutions and limited resources. This study enriches the child development model with an ecological and resilience perspective and offers guidelines for community-based interventions. In terms of policy, it is recommended to strengthen the synergy between the government, KPAI, and LSM through integrated monitoring and specific budget allocation for child protection in prostitution environments.